Accessibility to Talar Dome in Neutral Position, Dorsiflexion, or Noninvasive Distraction in Posterior Ankle Arthroscopy. (August 2019) - Hirtler, Lena; Schellander, Katarina; Schuh, Reinhard
Background: Osteochondral lesions of the talus are frequent pathologies of the ankle joint. Especially through arthroscopy, the treatment is kept as minimally invasive as possible. However, there are some drawbacks as to the reachability because of the high congruency of the ankle joint. Here, either noninvasive distraction or maximal dorsiflexion may be an option for better access to the lesion. The purpose of this study was to evaluate maximal dorsiflexion compared to neutral position or noninvasive distraction of the ankle joint in the arthroscopic reachability of the talar dome. The hypothesis of this study was that maximal dorsiflexion would allow for greater accessibility of the talar dome compared to neutral position or noninvasive distraction of the joint. Methods: Twenty matched pairs (n=40) of anatomical ankle specimens were used. The effects of neutral position, maximal dorsiflexion, and noninvasive distraction of the ankle joint on arthroscopic accessibility of the ankle joint were tested. After disarticulation of the talus, reach was measured and compared between the 3 positions. Results: In neutral position, 13.7±1.2 mm of the talar dome was reached laterally and 14.0±1.0 mm medially. In maximal dorsiflexion, the distance was 19.0±1.1mm laterally and 19.8±1.4 mm medially, and in noninvasive distraction it was 16.1±1.5 mm laterally and 15.7±1.0 mm medially. The statistical comparison showed a significantly better reach in dorsiflexion laterally ( P = .003) and medially ( P = .026). Conclusion: Accessibility of the talar dome in maximal dorsiflexion was superior to that in neutral position or noninvasive distraction. Clinical Relevance: Results of this study may allow for better planning in arthroscopic treatment of osteochondral lesions of the talus.